(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To evaluate hearing outcome after type I tympanoplasty in inactive mucous type of chronic otitis media. Methods: It was a cross-sectional study conducted in the department of Otolaryngology & Head Neck Surgery, Sir Salimullah Medical College and Mitford Hospital, Dhaka, from July 2014 to June 2016. 50 cases were selected by matching inclusion and exclusion criteria. Paired t-test and Z test was used to analyze the variables. P values <0.05 was considered as statistically significant. Results: The mean age was found 28.5 years with range from 15 to 41 years and male female ratio was 1.3:1. All patients had intermittent otorrhoea and varying degree of hearing loss. The mean air conduction threshold was 40.2 dB preoperatively and 27.1 dB post-operatively. Air-bone gap was found 26.9 dB in preoperative and 16.1 dB in post-operative group. The differences were statistically significant between preoperative and post-operative group. Thus mean improvement of air conduction threshold was 13.1 dB and air-bone gap was 10.8 dB. Two third (66.%) patients improved <15 db air conduction thresholds and 17(34%) improved ≥15 db air conduction thresholds. Using the proportion of patients with a postoperative hearing within 40 dB as the criterion, this study showed 46(92%) patients achieving this and 40(80%) patients achieving AB gap within 20 db postoperatively. Conclusion: Improvement of air conduction threshold and AB gap after type I tympanoplasty was statistically significant. Thus from this study it can be concluded that type I tympanoplasty is an effective technique for hearing improvement in inactive mucous type of chronic otitis media. Bangladesh J Otorhinolaryngol; April 2018; 24(1): 50-55